The fragmentation of expanding shells: III. oligarchic accretion and the mass spectrum of fragments - Dale, James; Wünsch, Richard; Smith, Rowan J.; Whitworth, Anthony; Palouš, Jan (Monthly notices of the Royal Astronomical Society, 2011)
We use smoothed particle hydrodynamics (SPH) simulations to investigate the gravitational fragmentation of expanding shells through the linear and non-linear regimes. The results are analysed using spherical-harmonic decomposition to capture the initiation of structure during the linear regime, the potential-based method of Smith et al. to follow the development of clumps in the mildly non-linear regime and sink particles to capture the properties of the final bound objects during the highly non-linear regime. In the early, mildly non-linear phase of fragmentation, we find that the clump mass function still agrees quite well with the mass function predicted by the analytic model. However, the sink mass function is quite different, in the sense of being skewed towards high-mass objects. This is because, once the growth of a condensation becomes non-linear, it tends to be growing non-competitively from its own essentially separate reservoir; we call this oligarchic accretion.